Nanostructured modified layered double hydroxides (LDHs)-based catalysts: A review on synthesis, characterization, and applications in water remediation by advanced oxidation processes - Karim, Ansaf V.; Hassani, Aydin; Eghbali, Paria; Nidheesh, P.V. (Current opinion in solid state & materials science, 2022)
[Display omitted] •Research advances of nanostructured modified LDHs-based catalysts are reviewed.•The synthesis, modification strategies, and characterization of nanostructured LDHs-based catalysts are summarized.•Nanostructured modified LDHs-based catalysts are promising candidates for various organic pollutants elimination in AOPs.•Mechanisms of pollutants elimination from water using nanostructured modified LDHs are described.•The challenges and prospects of nanostructured LDHs-based catalysts are proposed. Layered double hydroxides (LDHs) are emerging catalyst materials with inner layer water molecules and higher anion exchange capacity. They have been extensively used as catalyst materials owing to their high specific surface area, environmental friendliness, lower cost, and non-toxicity. However, the lower surface area and leaching of metal ions from LDHs composites reduce the process efficiency of the catalyst. Modifying the LDHs materials with other materials can improve the surface properties of the composite and enhance the catalytic performance. Herein, this review aims to summarize the recent progress of nanostructured modified LDHs materials, their classification, synthesis, and a detailed discussion on their characterization techniques. Further, this study also discusses the application of nanostructured modified LDHs materials as catalysts in advanced oxidation process (AOPs) for various organic pollutants removal.